Demographical Factors Related to The Nursing Students’ Stress at the University After COVID-19 Pandemic - Nur Fithriyanti Imamah; Ekadinata, Nopryan; Nikmah , Khairun; Nurhaliza, Siti; Triyani, Yuli (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Nursing students have affected by the COVID-19 pandemic through many changes in academic learning process. Yet, in the daily life, they also need to adjust the new life which might suppress several students. In this study, presumed that factors including gender, religion, level of semester, living status, and living arrangement would be related to the nursing student’s stress. A total of 237 nursing students from Bachelor degree, which have age higher than 17, and actively registered as students, have been involved in this study. The result showed that more than 50% respondents were female and experienced moderate level of stress. The result from Chi-Square test described that only one factor, the level of semester that has been related to the stress level. Other demographical factors were not statistically significant to the stress level. In each semester, students might face different stressors and used different coping strategies to deal with. This study highlighted the urge of need for nurses who works at the university healthcare centre or community nurses in designing stress management for nursing students based on their year academic level since the stressor might be different.